Tough love or unconditional charity? - Spiros Bougheas; Indraneel Dasgupta; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2005)
Charitable giving has increasingly become `tough love' - it has come to require recipients to undertake costly prior action. A common justification is that of greater efficiency: willingness to undertake costly actions signals greater productivity from transfers. However, there is a trade-off. Conditions impose a cost, since the activities required are by themselves welfare reducing for at least some of the beneficiaries. We present a simple model to demonstrate that, if the distribution of recipient types is unknown, recipient costs are indivisible and productivity unobservable, conditional charity, once instituted, may not yield information adequate to refute its efficiency claim. Consequently, donors who inefficiently provide conditional charity will not correct themselves. Donors who wrongly provide unconditional charity may however subsequently correct themselves. We thus offer grounds for scepticism regarding efficiency claims for conditional charity. Our analysis also provides reasons for encouraging donor multiplicity.
Keywords: F35; F34; I38; O20; 330; Tough love; Conditional Charity; Unconditional Charity; Donor Conditionality; Spende; Kosten; Theorie